Evaluation of the p16 and Ki-67 Biomarkers as Predictors of the Recurrence of Premalignant Cervical Cancer Lesions after LEEP Conization - Leite, Paulo Macêdo de Oliveira; Tafuri, Luciene; Costa, Maria Zélia de Oliveira; Lima, Maria Inês de Miranda; Simões, Renata Toscano (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Objective To evaluate the expressions of biomarkers p16 and Ki-67 in low-grade (LG) or high-grade (HG) lesions, and to relate them to risk factors and the recurrence of these lesions.Methods A retrospective case-control study of 86 patients with LG and HG lesions who underwent a loop electrosurgical excision procedure (LEEP) between 1999 and 2004. The control group was composed of 69 women with no recurrence, and the study group, of 17 patients with recurrence. All patients were followed-up over a two-year period after surgery, and screened every six months, including cytology and colposcopy. Biopsy samples collected from LEEP were submitted to immunohistochemical analysis for p16 and Ki-67. The statistical analysis was performed using the Statistical Package for the Social Sciences software (SPSS, IBM-SPSS, Inc., Chicago, IL, US), with a significant p ​​< 0.05.Results The biomarkers p16 and Ki-67, separately or combined, showed no relation to recurrence on the total analysis. However, evaluating specifically HG lesions, the positive expression (2+ and 3+) of p16/Ki-67 was associated with recurrence (0.010). In addition, p16 isolated was also more expressive in HG lesions (2+ and 3 + , p = 0.018), but it was unrelated to recurrence.Conclusion Proteins p16 and Ki-67, both isolated and combined, are not reliable primary markers for the recurrence of cervical lesions in the majority of LG lesions. However, analyzing only the group with prior diagnosis of HG lesions, the expressions of p16 and of p16/Ki-67 were associated with recurrence, and they may be useful in monitoring these cases.
Keywords: biomarkers; conization; cervical intraepithelial neoplasia; recurrence